Pengaruh variasi campuran bahan bakar plastik polypropylene (PP) dan pertalite terhadap performa unjuk kerja motor injeksi 110 cc - Aji Sangjoko; Nely Ana Mufarida; Kosjoko Kosjoko (Universitas Muhammadiyah Metro, 2023)
The worldwide generation of plastics evolved over the years due to the use of plastics in various sectors. This increase affects the availability of petroleum resources because plastic is a petroleum-based material. The research method used is the experimental method. In this study, observations and tests were carried out on the performance of the 110 cc injection motor, namely torque and power. Data collection begins with 3000 RPM rounds and ends with 8000 RPM rounds according to the standard. The mixing variations between pertalite fuel and polypropylene plastic fuel are as follows: 30% pertalite and 70% polypropylene, 40% pertalite and 60% polypropylene, 50% pertalite and 50% polypropylene. The results showed that the fuel mixture of 30% pertalite and 70% polypropylene experienced an increase in torque from 5.77 N.m to 14.06 N.m, and an increase in power from 1.9 HP to 7.4 HP.